Internet addiction among college students during the lockdown period of COVID-19 pandemic: An observational study from South India - Kannappa V Shetty; Chandra Shekar; Sanjeev Kumar; Palaniappan Marimuthu; K S Amritha; S Suparna; Urmila Bamney (Wolters Kluwer Medknow Publications, 2023)
Introduction: The COVID-19 epidemic has had and continues to have a profound medical, psychological, and social impact on people of all ages, causing a crisis effect on society. Adolescent's psychosocial status was badly influenced by pandemic control strategies like an extended absence from formal education and home seclusion, during which their Internet use increased significantly. Excessive usage of smartphones can cause serious health problems such as neck pain, accidents, sleep disruptions, and depression. Methods: A cross-sectional online survey was conducted among 201 students aged between 16 and 25. The data were collected using a structured questionnaire that was distributed over numerous online portals. The sociodemographic questionnaire and the Internet addiction test were used for the study. Results: The mean age of students was found to be 21.2 ± 7.38 years. Most of the participants were female (130, 65%), undergraduates (118, 59%) and were using mobile network as a modem of connectivity (163, 81%). The salience (92.98) and neglect work (39.34) subscales of Internet addiction were higher among nuclear family students. Internet addiction is positively correlated to the family income (0.149**) of students. Conclusion: The outcomes of the study imply that during a lockdown, students can be given psychological support.